The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00360-010-0544-0
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of development and hypoxia on catecholamine synthesis and cardiac function in zebrafish (Danio rerio)

Abstract: The rate-limiting enzyme in the biosynthetic pathway of catecholamines is tyrosine hydroxylase (TH), the activity of which is dependent on molecular oxygen. Zebrafish (Danio rerio) possess two non-allelic TH coding genes, TH1 and TH2. A principal goal of the present study was to determine if the expression of these genes is sensitive to environmental hypoxia. Additionally, we sought to determine if catecholamine content of larvae was changed by environmental hypoxia, and whether the hearts of hypoxic larvae we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 42 publications
5
16
1
2
Order By: Relevance
“…The dose of 0.05 mg ml −1 of MS-222 was chosen because it was the lowest dose able to keep the larvae immobilized. Other studies have shown that high doses of MS-222 decrease f H in zebrafish larvae; however, the concentration used in this study is lower than that used in those studies (Steele et al, 2009(Steele et al, , 2011. Furthermore, in our own experiments only a dose of MS-222 above 0.12 mg ml −1 caused a decrease in f H after 10-15 min exposure of 4 dpf larvae.…”
Section: Injection Of Ho-1 Morpholinocontrasting
confidence: 61%
See 3 more Smart Citations
“…The dose of 0.05 mg ml −1 of MS-222 was chosen because it was the lowest dose able to keep the larvae immobilized. Other studies have shown that high doses of MS-222 decrease f H in zebrafish larvae; however, the concentration used in this study is lower than that used in those studies (Steele et al, 2009(Steele et al, , 2011. Furthermore, in our own experiments only a dose of MS-222 above 0.12 mg ml −1 caused a decrease in f H after 10-15 min exposure of 4 dpf larvae.…”
Section: Injection Of Ho-1 Morpholinocontrasting
confidence: 61%
“…Following the hypoxic treatment, larvae were exposed to hypoxic water containing either 40 µmol l −1 CORM or 10 −4 mol l −1 adrenaline for an additional 15 min. The adrenaline concentration used was based on a previous study (Steele et al, 2011) and preliminary trials which demonstrated that it was the lowest concentration to reliably produce a positive cardiac chronotropic effect. The CORM concentration was chosen based on dose−response curves performed with concentrations used previously in mammals (Clark et al, 2003).…”
Section: Injection Of Ho-1 Morpholinomentioning
confidence: 99%
See 2 more Smart Citations
“…Catecholamines either can interact with target cells after their secretion as neurotransmitters from nearby nerve endings, or after their release from chromaffin cells for more widespread distribution via the circulatory system. Using high-performance liquid chromatography (HPLC), catecholamines were detectable in whole embryos at 1 h post fertilization (hpf), presumably derived from maternal transfer (Steele et al, 2011). At 2 days post fertilization (dpf), chromaffin cells were found to be dispersed as clusters in the inter-renal organ, which then converged to midline by 3 dpf; the chromaffin cells stay in intimate contact with steroidogenic cells throughout the subsequent development (Liu, 2007;To et al, 2007).…”
Section: Catecholaminesmentioning
confidence: 98%